Модель апаратно-програмной тестовой платформы для ПЛК - Мельник, Е. Ю. (ХНУРЭ, 2019)
The model of hardware and software platform for the PLC, we organize the purpose of the PLC and try to understand the places where this device is used. we define the types of modular layouts for creating an existing system for testing the correctness of the PLC operation or for training a specialist. We investigate the chosen model and determine its components, and draw conclusions about the need to create new layouts for testing, more focused and more unique to avoid accidents on real systems, and to train specialists on visual premiers for higher qualifications.
Keywords: ПЛК; тестова платформа